Re-administration of abatacept for the control of articular symptoms of rheumatoid arthritis during anti-tuberculous therapy. (2017) - Kawamoto, Hironori; Takasaki, Jin; Ishii, Satoru; Suzuki, Manabu; Morino, Eriko; Naka, Go; Iikura, Motoyasu; Izumi, Shinyu; Takeda, Yuichiro; Sugiyama, Haruhito
Abstract: This case report describes the re-administration of abatacept to successfully reduce the articularsymptoms of a patient with rheumatoid arthritisduring the intensive phase of anti-tuberculous therapy. A 75-year-old man developed active pulmonary tuberculosis during the administration of abatacept for rheumatoid arthritis. The patient experienced a paradoxical reaction and exacerbation of rheumatoid arthritis that caused us to discontinue the abatacept. Later re-administration of abatacept along with anti-tuberculosis treatment led to well-controlled rheumatoid arthritis without exacerbation of the tuberculosis. This case shows that re-administration of abatacept may be much safer than TNF inhibitor to treat patients who are infected with mycobacteria during thetreatment of immunological diseases such asrheumatoid arthritiswith biological agents.